KREDIT BERMASALAH PADA KOPERASI SIMPAN PINJAM BHUANA ARTHA MULIA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - I Gusti Ayu Ratih Permata Dewi (Fakultas Ekonomi, Program Studi Akuntansi, Universitas Warmadewa, 2022)
The Bhuana Arta Mulia Savings and Loans Cooperative provides credit to borrowers, if the cooperative feels confident that the credit given to prospective customers will be received according to the terms and conditions that have been agreed by both parties. If there are one or more debtors who do not comply with these rules, it can have an impact in the future, namely the kupedes given are not in accordance with the stipulated time or the payment will be in arrears. In general, there are two factors that cause non-performing loans, namely internal factors and external factors. This study wants to know the internal and external factors that influence the non-performing loans in the Bhuana Arta Mulia Savings and Loan Cooperative. The population in this study were customers of the Bhuana Arta Mulia Savings and Loan Cooperative. Determination of the research sample can use the Slovin formula. The data collection technique in this study was a questionnaire. The data analysis technique used is multiple linear regression analysis. The results show that internal factors have no effect on non-performing loans. Meanwhile, external factors affect non-performing loans.